Efficiency of narrow band ultraviolet B in treatment of refractory renal pruritus among patients on hemodialysis - خدام, جمال (Latakia University Journal -Medical Sciences Series, 2022)
Objective: Evaluate the efficacy of narrowband ultraviolet B (nb-UVB) phototherapy in the treatment of refractory renal pruritus among patients on hemodialysis. Methods: The study enrolled 35 patients suffering from chronic renal disease and undergoing hemodialysis, who experienced severe pruritus nonresponsive to conventional treatments. These patients were treated with nb-UVB phototherapy 3 times a week for 4 months. Pruritus was evaluated monthly during treatment, and 3 months after the end of treatment using 12-item of pruritus severity scale (12-PSS). Results: There was a significant improvement in the severity of itching after the first three months of nb-UVB phototherapy, but the improvement at the fourth visit was not satisfactory. The mean 12-PSS value decreased from 19.6 ±1.8 before the treatment to 9.4 ±3.8 at the end of the treatment (p-value <0.001), but increased to 12.6 ±3.9 after 3 months after the end treatment. The total response rate was 82.9%. Although the recurrence rate was 44.8%, the overall improvement was significant compared to the condition before treatment (p-value <0.001). Conclusion: The treatment of nb-UVB phototherapy for refractory renal pruritus in dialysis patients is effective, beneficial and safe even if a complete response is not achieved.